Quality Properties Of Activated Charcoal Of Bidara Wood (Ziziphus Mauritiana) With The Addition Of ????? Solution Based On Activation Temperature Variation - Naurah Fadillah Azzahra; Devi Tanggasari (Protech Biosystems Journal, 2024)
One of the materials that can be used to make activated charcoal is bidara wood. Bidara wood has a high carbon content and a good pore structure. In addition, bidara wood also contains several minerals such as calcium, potassium, and magnesium in small amounts. The content of these compounds and elements makes bidara wood very suitable to be used as a raw material for activated charcoal. One of the activation materials is an H3PO4 solution. In the activation process, bidara wood activated charcoal can improve its quality properties, such as surface area, pore volume, and adsorption capacity. Therefore, the aim of this research is to determine the effect of heating temperature variations on the quality properties of bidara wood activated charcoal using chemical activation with an H3PO4 solution. The experimental design used in this study is a Completely Randomized Design with one factor, which is the activation temperature (500, 600, and 700˚C). The results of the study showed that the use of H3PO4 solution at a temperature variation of 700˚C resulted in better properties for moisture content (5.41%), ash content (43.29%), and iodine adsorption capacity (4,737 mg/g) compared to the temperature variations of 500˚C and 600˚C.